2000
DOI: 10.1126/science.288.5463.128
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotopic Evidence for Methane Hydrate Instability During Quaternary Interstadials

Abstract: Large (about 5 per mil) millennial-scale benthic foraminiferal carbon isotopic oscillations in the Santa Barbara Basin during the last 60,000 years reflect widespread shoaling of sedimentary methane gradients and increased outgassing from gas hydrate dissociation during interstadials. Furthermore, several large, brief, negative excursions (up to -6 per mil) coinciding with smaller shifts (up to -3 per mil) in depth-stratified planktonic foraminiferal species indicate massive releases of methane from basin sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
343
4
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 510 publications
(370 citation statements)
references
References 63 publications
12
343
4
6
Order By: Relevance
“…The minimal volume of methane degassed and oxidized in the water column during the main event at Ϸ39 ka is estimated at Ϸ5.5 ϫ 10 9 m 3 . ʈ It corresponds to Ϸ4 Tg (teragrams) of methane, which is approximately two to three times higher than estimates made for the Santa Barbara Basin (6). The lack of a watercolumn vertical gradient in the ␦ 13 C record and the long stratigraphic extension of these anomalies indicate that these inferred emissions were sustained for a period longer than a few generations of foraminifera.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The minimal volume of methane degassed and oxidized in the water column during the main event at Ϸ39 ka is estimated at Ϸ5.5 ϫ 10 9 m 3 . ʈ It corresponds to Ϸ4 Tg (teragrams) of methane, which is approximately two to three times higher than estimates made for the Santa Barbara Basin (6). The lack of a watercolumn vertical gradient in the ␦ 13 C record and the long stratigraphic extension of these anomalies indicate that these inferred emissions were sustained for a period longer than a few generations of foraminifera.…”
Section: Discussionmentioning
confidence: 74%
“…The accepted hypothesis of a strong link between climate and methane emissions from wetlands was called into question recently by an exhaustive review of the timing and extension in the geological record of these wetlands (4), as well as by numerical simulations of the global carbon cycle (5). Finally, two independent geochemical proxies, the isotopic composition of foraminifera (6) and the molecular composition of the organic matter (7), shed light on the potential role of large methane releases from gas-hydrate dissociation as an important source in the oceanic global carbon cycle. These two records from the Santa Barbara Basin have shown that these inferred methane releases occurred during the last glacial episode in response to a warming of the intermediate waters and thus presumably of the deep-sea sediments.…”
mentioning
confidence: 99%
“…Hydrocarbon reservoirs in the Santa Barbara Basin have been leaking fluids and gas for the past 60 000 of years (Kennett et al, 2000), which produced distinct seafloor morphologies such as active gas vents, pockmarks, tar-flows, and carbonate mounds and pavement (Figs. 2, 8a, b, c, and 9).…”
Section: Fluid Flowmentioning
confidence: 99%
“…Negative ␦ 13 C shifts recorded in planktonic foraminifera during rapid interstadial warming events in SBC have been interpreted as destabilization of methane hydrates and release of methane to the water column and atmosphere (11). In addition, ␦ 13 C values and radiocarbon dating of foraminifera from a pockmark near modern seeps in SBC suggest gas emissions during the last 25,000 years (25 ky) (12).…”
mentioning
confidence: 99%